UJI ZPT HANTU TERHADAP PERTUMBUHAN DAN PRODUKSI SELADA MERAH (Lactuca sativa) - Seprita Lidar; Enny Mutryarny (Jurnal Ilmiah Pertanian, 2017)
Lettuce plants is one of the vegetables that have commercial value and goodprospects for development, because demand for lettuce plants continues to increasein line with population growth and awareness of nutritional needs and thedevelopment of such culinary business. Red lettuce new red fire red to black curlyleaves, the red if given full sun. This type of lettuce is not widely grown in Riau,when environmental conditions allow, the problem is the type of Ultisol, then toovercome it is to the development of good farming such as the provision of plantgrowth regulator (PGR) Hantu. Hantu PGR containing gibberellic acid, IndolAcetic Acid, Kinetin and Zeatin. The research objective was to determine the effectand get the best Hantu PGR concentration on the growth and production of redlettuce. Research conducted experiments with completely randomized design with 5 level of treatment that is without giving PGR Hantu (H0), the provision of 1 ml / l of water (H1), administration of 2 ml / l of water (H2), giving 3 ml / l water (H3) and the provision of 4 ml / l of water (H4) to four (4) replicates. Data were analyzed by analysis of variance followed by a further test DMRT level of 5%. The results showed that the Hantu PGR can promote the growth and production of red lettuce plants, with the best concentration was 2 ml / l of water.